The Influence of Governance, Risk and Compliance (GRC) and Company Characteristics on Financial Performance with Moderation of IT Investment in the Era of Digitalization - Dewi, Febriana Candra; Aryati, Titik (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The study aims to determine the influence of Governance, Risk and Compliance (GRC) and company characteristics proxied by firm size, leverage, and sales growth on the company's financial performance, and to determine its influence when moderated by IT investment in the digitalization era in consumer goods industry sector companies listed on the IDX in 2019-2022. To achieve these objectives, the study was conducted using quantitative methods multiple linear regression methods, and using purposive sampling techniques for sampling. The data samples used in this study were 86 samples that were free from outlier data. Based on the evaluation results, it was found that GRC did not affect financial performance. Leverage had a negative effect on financial performance. While firm size and sales growth had a positive effect on financial performance. Then it was found that IT investment had no effect in strengthening the influence of GRC, firm size, and sales growth on financial performance, but IT investment could reduce the negative effect of leverage on the company's financial performance.